Intracytoplasmic sperm injection is not superior to conventional IVF in couples with non-male factor infertility and preimplantation genetic testing for aneuploidies (PGT-A). Issue 2 (22nd February 2020) - De Munck, Neelke; El Khatib, Ibrahim; Abdala, Andrea; El-Damen, Ahmed; Bayram, Aşina; Arnanz, Ana; Melado, Laura; Lawrenz, Barbara; Fatemi, Human M
Abstract: STUDY QUESTION: Does the insemination method impact the euploidy outcome in couples with non-male factor infertility? SUMMARY ANSWER: Conventional IVF can be applied in cycles with preimplantation genetic testing for aneuploidies (PGT-A), as both IVF and ICSI generate equal numbers of euploid blastocysts. WHAT IS KNOWN ALREADY: Ever since its introduction, the popularity of ICSI has increased tremendously, even in couples with non-male factor infertility. The use of conventional IVF is a contraindication for couples undergoing PGT to ensure monospermic fertilisation and to eliminate potential paternal contamination from extraneous sperm attached to the zona pellucida. Despite this, it has recently been shown that sperm DNA fails to amplify under the conditions used for trophectoderm biopsy samples. STUDY DESIGN, SIZE, DURATION: This single-centre prospective pilot study included 30 couples between November 2018 and April 2019. PARTICIPANTS/MATERIALS, SETTING, METHOD: Arab couples, with a female age between 18–40 years, body mass index ≤30 kg/m 2, at least 10 cumulus oocyte complexes (COCs) following oocyte retrieval (OR) and normal semen concentration and motility (WHO) in the fresh ejaculate on the day of OR, were eligible for the study. Half of the sibling oocytes were assigned to conventional IVF, and the other half were assigned to ICSI. All embryos were cultured in a time-lapse imaging system in Global Total LP media. Blastocysts were subjected to trophectoderm biopsy on Day 5, 6 or 7 and next-generation sequencing (NGS) to determine blastocyst ploidy status. The primary objective was to determine the euploid rate in blastocysts from sibling oocytes. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 568 COCs were randomly allocated between IVF ( n = 283; 9.4 ± 4.0) and ICSI ( n = 285; 9.5 ± 4.1). While the incidence of normal fertilisation per cycle (6.1 ± 3.8 (64.0%) vs 6.3 ± 3.5 (65.4%); P = 0.609) was distributed equally between IVF and ICSI, the degeneration rate (0.1 ± 0.3 vs 0.7 ± 0.8; P = 0.0003) was significantly higher after ICSI and the incidence of abnormal fertilisation (≥3 pronuclei) was significantly higher after IVF (0.9 ± 1.2 vs 0.2 ± 0.4; P = 0.005). For all fertilised oocytes, there were no differences in the number of good-quality embryos on Day 3 (74% vs 78%; P = 0.467), nor in the blastulation rate on Day 5 (80.4% vs 70.8%; P = 0.076). The total number of blastocysts biopsied per cycle on Days 5, 6 and 7 was not significantly different between IVF or ICSI (4.0 ± 2.8 vs 3.9 ± 2.5; P = 0.774). With euploid rates of 49.8 and 44.1% ( P = 0.755; OR: 1.05664 [0.75188–1.48494), respectively, there was no significant difference identified between IVF and ICSI (2.0 ± 1.8 vs 1.9 ± 1.7; P = 0.808) and all couples had at least one euploid blastocyst available for transfer. When considering only euploid blastocysts, the male/female ratio was 61/39 in IVF and 43/57 in ICSI ( P = 0.063). LIMITATIONS, REASON FOR CAUTION: This is a pilot study with a limited patient population of 30 couples (and 568 COCs) with a normal ovarian response. The results of our study should not be extrapolated to other patient populations. WIDER IMPLICATIONS OF THE FINDINGS: It is safe to apply conventional IVF in couples with non-male factor infertility undergoing PGT-A. STUDY FUNDING/COMPETING INTEREST(S): No funding was obtained. There are no competing interests. TRIAL REGISTRATION NUMBER: NCT03708991.